Knee Instability and Basic and Advanced Function Decline in Persons with Knee Osteoarthritis - Sharma, Leena (Arthritis Care Res (Hoboken), 2015)
OBJECTIVE: Manifestations of instability in knee OA include low overall knee confidence, low confidence that the knees will not buckle, buckling, and excessive motion during gait. Confidence and buckling may particularly influence activity choices, contributing to events leading to disability. Buckling is more likely to affect advanced than basic functional tasks. In this prospective, longitudinal study, we tested the hypotheses: overall knee confidence, buckling confidence, buckling, and frontal plane motion during gait are associated with advanced 2-year function outcome in persons with knee OA. METHODS: Persons with knee OA were queried about overall knee confidence (higher worse), buckling confidence, and knee buckling, and underwent quantitative gait analysis to quantify varus-valgus excursion and angular velocity. Physical function was assessed using the LLFDI Basic and Advanced Lower Extremity Domain scores. Logistic regression was used to evaluate the relationship between baseline instability measures and baseline-to-2-year function outcome, adjusting for potential confounders. RESULTS: 212 persons (mean age 64.6 years, 76.9% women) comprised the sample. Buckling was significantly associated with poor advanced (adjusted OR 2.08, 95% CI: 1.03–4.20) but not basic function outcome. Overall knee confidence was significantly associated with advanced outcome (adjusted OR 1.65, 95% CI: 1.01–2.70), while associations between buckling confidence and both outcomes approached significance. Neither varus-valgus excursion nor angular velocity during gait was associated with either outcome. CONCLUSION: Knee buckling and confidence were each associated with poor 2-year advanced function outcome. Current treatment does not address these modifiable factors; interventions to address them may improve outcome in knee OA.